Differential Culturability of Mycobacterium tuberculosis in Culture-Negative Sputum of Patients With Pulmonary Tuberculosis and in a Simulated Model of Dormancy - Dusthackeer, Azger; Balasubramanian, Magizhaveni; Shanmugam, Govindarajan; Priya, Shanmuga; Nirmal, Christy Rosaline; Sam Ebenezer, Rajadas; Balasubramanian, Angayarkanni; Mondal, Rajesh Kumar; Thiruvenkadam, Kannan; Hemanth Kumar, A. K.; Ramachandran, Geetha; Subbian, Selvakumar (Frontiers in Microbiology, 2019)
Tuberculosis (TB) remains a leading killer among infectious diseases of humans worldwide. Delayed diagnosis is a key problem in global TB control programs. Bacteriological methods currently used to diagnose TB in endemic countries takes up to 8 weeks that poses significant delay in starting antibiotic therapy. Presence of a heterogeneous population of Mycobacterium tuberculosis, the causative agent of TB, is among the reasons for delayed diagnosis by bacteriological methods. Previously, it has been shown that mycobacterial resuscitation promoting factors (RPF), a family of proteins secreted by actively growing bacteria into the media, are capable of activating the growth of dormant bacteria, thus enhancing the detection of bacilli in the sputum of confirmed TB cases. However, the variability in bacterial resuscitation by RPF in the sputum of suspected pulmonary TB cases that showed differential smear and/or culture positivity during diagnosis has not been fully explored. Here, we report the presence of non-replicating bacteria in the sputum of suspected TB cases that show differential growth response to RPF treatment. Using crude and recombinant RPF treatment, we show improved sensitivity and reduced time to detect bacilli in the sputum samples of smear-positive/culture-negative or smear-negative/culture-negative cases. We also report the phenotypic heterogeneity in the RPF-responsiveness among Mtb strains using an in vitro dormancy model. Our findings have implications for improving the bacteriological diagnostic modalities currently used to diagnose TB in endemic countries.